“Some Do it Out of Necessity, Others Because They Like Money and Others Because They Find it Easy”: Motivations for the Involvement of Women in Drug Trafficking in Peru - (:unkn) unknown (Taylor & Francis, 2024)
Latin American feminist scholars have constructed valuable analyses on how structural inequalities, feminization of poverty, and patriarchy are the main reasons women get involved in drug trafficking. As the primary material and emotional providers of th...
Keywords: Tráfico de drogas; Mujeres